A STELLA Model for Evaluating the Efficiency of Integrated Multi Trophic Aquaculture System (IMTA) - Kambey, Cicilia; Chung, Ik Kyo (Indonesian Aquaculture Society (MAI), 2015)
There has been ever increasing interest in Integrated Multi-Trophic Aquaculture System (IMTA) to encourage developing environmentally friendly aquaculture, which combines fed aquaculture with extractive aquaculture in proximity. IMTA can minimize the environmental impacts of conventional monoculture aquaculture farms while expanding their economic base. To evaluate the efficiency of IMTA system, we applied the dynamic STELLA modeling in terms of nitrogen content of each component. Consequently we may develop potential strategic guidelines of IMTA implementation which may increase the managing and predictive capability and the social acceptability of the system.Keywords: STELLA modeling; IMTA; Nitrogen; Fish; Bivalve; Seaweed; Sea Cucumber